Using a Text-Based Discussion Instructional Strategy in the Teaching of Reading in Arabic as A Foreign Language - Harison Mohd Sidek; Hazrimah Ab. Rahim (Universiti Sains Islam Malaysia, 2024)
Reading comprehension in Arabic as u foreign language (AFL) could be a challenging task to Arabic language learners especially among limited proficient learner. One of the ways to assist AFL learners in reading comprehension is by using an instructional approach that nurtures efficiency in information processing via guided and meaningful interaction. Students' reading comprehension ability when reading in a foreign language has been an area of interest in the field of' second language trading. In lieu of this concern, this paper attempts to discuss the more comprehensive theoretical and conceptual framework of a text-based reading comprehension instruction as a reading instructional model that might have potential to l assist AFL readers enhance their reading ability. The instructional model presented in this paper,for AFL reading instruction is adapted from English as a first language reading instructional model. The specific procedures in implementing the adapted model are also provided.